Immigrants in a multicultural and postmodern world: multiculturalism in Zadie Smith’s White Teeth and The Autograph Man - Drishti, Maisha Tasneem (Brac University, 2022)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Masters of Arts in Teaching to Speakers of Other Languages, 2021.